Design and Build Smart Aquascape Based on PH and TDS With IoT System Using Fuzzy Logic - Muhammad Fikri; Aziz Musthafa; Faishal Reza Pradhana (Procedia of Engineering and Life Science, 2021)
Acid (pH) and Total Dissolve Solid (TDS) are the two most important factors of the many parameters that must be considered to maintain water quality in Aquascape. A good normal pH for plant life in Aquascape is 6.8 and a good TDS for water in aquascape is below 150 ppm. This study aims to design an IOT system to maintain the pH and TDS of water in aquascapes. In this study using the fuzzy method as a controller and determinant of the added value of acid or wet water in the aquascape. The pH set in this system is between 6.5-7.3. This system maintains the pH by adding alkaline or acidic water into the aquascape, so that the pH of the water in the aquascape is at a predetermined safe limit. the TDS system will drain the water in the aquascape, and add water with a lower TDS level. By calculating how many additions are right to keep the TDS of water in the aquascape at 150ppm. The result of this research is a system design that is able to control the pH and TDS of water in Aquascape.